2015
DOI: 10.1128/aac.01638-15
|View full text |Cite
|
Sign up to set email alerts
|

Two Simple Rules for Improving the Accuracy of Empiric Treatment of Multidrug-Resistant Urinary Tract Infections

Abstract: The emergence of multidrug-resistant (MDR) uropathogens is making the treatment of urinary tract infections (UTIs) more challenging. We sought to evaluate the accuracy of empiric therapy for MDR UTIs and the utility of prior culture data in improving the accuracy of the therapy chosen. The electronic health records from three U.S. Department of Veterans Affairs facilities were retrospectively reviewed for the treatments used for MDR UTIs over 4 years. An MDR UTI was defined as an infection caused by a uropatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
5
27
0
Order By: Relevance
“…When choosing empiric treatment in these settings, the provider should refer to the results of prior urine cultures if any are available. A study done in predominantly older men with UTI caused by MDRO found that prior urine culture results, even those collected as long ago as two years from the index case, were useful at predicting the causative pathogen and its susceptibilities [70]. …”
Section: Treatment Of Utismentioning
confidence: 99%
“…When choosing empiric treatment in these settings, the provider should refer to the results of prior urine cultures if any are available. A study done in predominantly older men with UTI caused by MDRO found that prior urine culture results, even those collected as long ago as two years from the index case, were useful at predicting the causative pathogen and its susceptibilities [70]. …”
Section: Treatment Of Utismentioning
confidence: 99%
“…The latter approach can be reasonably successful for E. coli isolates (since most are susceptible, even among hospital isolates) but has to be done with caution when treating other gramnegative species since CLSI interpretive criteria exist only for E. coli and Enterococcus faecalis urine isolates [21,30]. Some epidemiologic data have suggested that susceptibility to routinely tested agents like ciprofloxacin or TMP-SMX can be used as a marker for likely susceptibility to fosfomycin, but it is not uniform [5].…”
Section: Fosfomycin Tromethaminementioning
confidence: 99%
“…Clinicians considering treatment with TMP-SMX should carefully review an ambulatory patient's individual risk of MDR pathogenesis in addition to considering local resistance patterns prior to prescribing. In patients with UTIs caused by MDR pathogens, choosing an agent concordant with previous uropathogen microbiologic data may increase the chance of providing active empiric therapy [5].…”
Section: Trimethoprim-sulfamethoxazolementioning
confidence: 99%
See 1 more Smart Citation
“…(3941) Knowledge of an individual’s past culture data and related risk for antibiotic-resistant infection is a crucial part of appropriate antibiotic selection for a given patient. (40, 42, 43) A combined approach to SAP based on procedure-specific risks in conjunction with a patient’s own prior culture data could potentially serve to improve clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%